Produção de fitase por Rhizopus microsporus var. microsporus: purificação, caracterização bioquímica e aplicação - Sato, Vanessa Sayuri [UNESP] (2015)
Biotechnological research, and the application of enzymes in combination with the use of genetic engineering has been carried out in microorganisms for the production of enzymes for industrial purposes. Among these enzymes, microbial phytases, which catalyze the hydrolysis of phytate (myo-inositol hexakisphosphate) to myo-inositol and inorganic phosphate, have been widely used in animal feed. In this context, the fungus R. microsporus var. microsporus was selected as a good producer of the phytase with higher production levels when grown on Biofilm Fermentation (FB) (261,30 U/mg), using sugarcane bagasse as carbon additional source. The morphology of biofilms on inert support was examined by SEM observing interconnected hyphae forming an ordered array in the presence of many channels which enables efficient exchange of nutrients and oxygen. The extracellular phytase was purified 4.18 fold with 4.78% recovery. A single protein band was obtained in 6% PAGE and confirmed by 12% SDS-PAGE as a single protein band with 34 kDa. The optimum temperature for activity was 55 °C and the optimum pH 4.5. It was completely stable at temperatures between 30 °C and 40 °C for 120 min had low pH with a residual activity of over 50% between pH 3.0 and 5.0 for 60 min. The enzyme was activated by Ca2+ and inhibited by Zn2+. The enzyme was able to hydrolyze sodium phytate with a Km=0.72 mM, Vmax= 94.55 U/mg of protein. The crude extract containing phytase was dried using Spray Dryer with different adjuvants. Soybean meal and corn meal allowed the best recovery of phytase activity 60% and 59.5%, respectively. Considering the use of these two adjuvants, the optimum pH of activity for phytase in the dry extract was 4.5 and 8.5, respectively, and the optimum of temperature of 45-50 °C. When used corn meal, the stability was maintained above 90% at pH 2.5-10.0 for 60 min. The dry phytase (corn meal) was applied to the feed...